The Implementation of the Curriculum of Love as a Holistic Approach to Enhancing Early Childhood Well-being - Ni Wayan Risna Dewi; Ni Made Sri Laksmi (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
The systematic implementation of a curriculum oriented towards child welfare is still not supported by adequate empirical evidence. Limited research on implementing the Love Curriculum as a holistic pedagogical approach has resulted in a less than optimal understanding of its contribution to improving early childhood welfare. This study aims to analyse the implementation of the Love Curriculum as a holistic approach to improving the welfare of early childhood. The study used a mixed-methods approach with a sequential explanatory design. The study subjects numbered 280 participants, consisting of 5 heads of early childhood education units, 25 teachers, 125 children aged 5-6 years, and 125 parents. Data were collected through questionnaires, observations, interviews, and document analysis using the Love Curriculum implementation observation sheet instruments, child welfare observation instruments, interview guidelines, and documentation. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed with thematic analysis and integrated through joint displays. The results showed that the implementation of the Love Curriculum was in the high category, with positive teacher-child relationships as the highest dimension, while school-family collaboration still needs strengthening. In conclusion, the curriculum implementation supports the creation of a culture of care, play-based learning, a safe learning environment, and increased child engagement and well-being. The research implications suggest that the Love Curriculum can serve as a foundation for developing more humanistic, inclusive, and child-welfare-oriented early childhood education policies and practices.